Optimasi Persediaan Barang dengan Pendekatan Theory Of Constraints, Heuristic Silver Meal, dan Least Unit Cost untuk Meminimalkan Biaya - Selvia Antinah (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2024)
The aim of this research is to carry out inventory control and determine the results of optimal inventory costs using the Theory of Constraints (TOC), Silver Meal Heuristic and Least Unit Cost approaches to minimize costs. The method used in this research, namely Theory of Constraints (TOC), is a management approach that aims to identify and overcome obstacles or constraints that limit company productivity and efficiency. The Silver Meal heuristic in selecting the optimal lot size is by looking at the minimum cost of each period, while the Least Unit Cost looks at the minimum cost of each unit, both methods for determining the number of orders and appropriate inventory planning. The Heuristic Silver Meal and Least Unit Cost methods can minimize storage costs by ordering raw materials 12 times in one year, compared to the company's previous policy of placing orders 6 times in one year so that the company can reduce storage costs by IDR. 5,750,220,504.